Analysis of rice production in Panama: 1999-2016 - Sánchez-Galán Quintero, Enrique Alejandro (2020)
The national rice production is essential to guarantee food security, insofar as it is the main food of the Panamanian diet, meanwhile 93 % of Panamanians eat 158 g of rice per day. Panama lost rice’s self-sufficiency in 2004 and according to the analysis of subsequent years (2004-2016), there is no evidence of a reaction through a structured sectorial policy aimed to recover it. This research describes the national rice sector from 1999 to 2016, with the objective of knowing the limitations that may be revealed, to be able to react through a sectorial policy.